Do infants fed directly from the breast have improved appetite regulation and slower growth during early childhood compared with infants fed from a bottle? - Fisher Jennifer O; Collins Bradley N; DiSantis Katherine I; Davey Adam (BMC, 2011)
Abstract Background Behavioral mechanisms that contribute to the association between breastfeeding and reduced obesity risk are poorly understood. The purpose of this study was to evaluate the hypothesis that feeding human milk from the breast (direct breastfeeding) has a more optimal association with subsequent child appetite regulation behaviors and growth, when compared to bottle-feeding. Methods Children (n = 109) aged 3- to 6- years were retrospectively classified as directly breastfed (fed exclusively at the breast), bottle-fed human milk, or bottle-fed formula in the first three months of life. Young children's appetite regulation was examined by measuring three constructs (satiety response, food responsiveness, enjoyment of food) associated with obesity risk, using the Child Eating Behavior Questionnaire. Multinomial logistic regression analyses were used to test whether children bottle-fed either human milk or formula had reduced odds of high satiety and increased odds of high food responsiveness and high enjoyment of food compared to children fed directly from the breast. Current child weight status and growth trends from 6-36 months were also examined for their relation to direct breastfeeding and appetite regulation behaviors in early childhood. Results Children fed human milk in a bottle were 67% less likely to have high satiety responsiveness compared to directly breastfed children, after controlling for child age, child weight status, maternal race/ethnicity, and maternal education. There was no association of bottle-feeding (either human milk or formula) with young children's food responsiveness and enjoyment of food. There was neither an association of direct breastfeeding with current child weight status, nor was there a clear difference between directly breastfed and bottle-fed children in growth trajectories from 6- to 36-months. More rapid infant changes in weight-for-age score were associated with lower satiety responsiveness, higher food responsiveness and higher enjoyment of food in later childhood Conclusion While direct breastfeeding was not found to differentially affect growth trajectories from infancy to childhood compared to bottle-feeding, results suggest direct breastfeeding during early infancy is associated with greater appetite regulation later in childhood. A better understanding of such behavioral distinctions between direct breastfeeding and bottle-feeding may identify new pathways to reduce the pediatric obesity epidemic.